ECOWAS Interventions in Cote D’ivoire: The Dynamics of Nigeria’s Contributions - Obono, Itam Nnaghe; Aliegba, Eugene T.; Baban’umma, Mohammed Bello (Kashere Journal of Politics and International Relations, 2024)
ECOWAS has identified political and economic mismanagement of member states by political elites as the major cause of conflicts in the sub-region and has developed protocols and ECOWAS Conflict Prevention Framework for constructive engagements in crisis situations. The reluctance by Nigeria to lead ECOWAS military interventions to restore political stability between 1999 and 2012 in Guinea, Guinea Bissau, and Cote d’Ivoire, reverberated in the continent and global discourse and many scholars described it as a sign of fatigue and withdrawal by Nigeria from peacekeeping. This thesis examined Nigeria’s leadership role and ECOWAS interventions in Cote d’Ivoire. Through a descriptive qualitative case study design, in depth oral interviews of fifteen (15) selected respondents were reviewed as primary data and extensive documented sources in the case study as secondary data, were analyzed and utilized. The regional leading power theory was adopted to evaluate the strategies adopted in the sub-region to establish order and the nature of interactions between the member states. The results show that, the root cause of the crisis in Cote d’Ivoire was the politics of exclusion based on ethnicity, and with the French involvement, Nigeria opted for diplomacy, mediation and electoral assistance as measures to resolve the crisis. ECOWAS coordination was weak. However, with the region still plagued with internal security challenges, terrorism, smuggling, illicit cross border trading and political instability occasioned by bad governance, only dialogue and domestication of ECOWAS good governance protocols can ensure the attainment of ECOWAS goals.